The Influence of Situational Factors (Interpersonal Influence, Visual Appeal, Portability) and Reaction Factors (Hedonic Browsing and Utilitarian Browsing) on ​​Impulsive Buying in Shopee Users. - Rachmawati, Indira; Pertiwi, Mita Aren (International Journal of Environmental, Sustainability, and Social Science, 2026)
The year-end shopping campaign succeeded in encouraging many consumers to access mobile commerce. One of the mobile commerce that carries out this campaign is Shopee. Shoppe reported that the campaign managed to increase orders for local products up to six times from before. Looking at consumer behavior formed during online shopping festivals, two online shopper personalities were found which were reflected in this research, namely planned shopper and impulsive shopper. From the survey, it is known that 42 percent of planned shoppers admit to spending more during online shopping festivals. This study aims to determine the influence of situation factors (interpersonal influence, visual appeal, portability) and reaction factors (hedonic browsing and utilitarian browsing) on Impulsive buying on Shopee users. Collecting research data by distributing online questionnaires to 400 respondents and processing data using PLS-SEM. The results showed that all hypotheses were accepted except Visual Appeal which did not have a positive and significant effect on Utilitarian Browsing and Portability did not have a positive and significant effect on Hedonic Browsing.